PENGARUH KOMPENSASI FINANSIAL DAN KOMPENSASI NON- FINANSIAL TERHADAP KINERJA KARYAWAN PADA PT. ANGKASA PURA I (PERSERO) BANDAR UDARA INTERNASIONAL NGURAH RAI BALI - Gusti Agung Wulan Permata Sari; Luh Gede Leli Kusuma Dewi; Ni Putu Eka Mahadewi (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2016)
Compensation is everything that constitutes the benefits earned by employees in cash of money or something given directly (financially) or indirect (non-financial) which aimed for reciprocation that given from company on the results of employee performance at work. Compensation can be provided in financial and non-financial. Which including in the financial compensation are salary, bonuses, holiday allowances, superannuation. While that including in non-financial compensation are promotion opportunities, good colleagues, work environment, as well as a special achievement. The sample of this study is specified using purposive sampling technique using the theory of J Supranto with a total of 150 respondents focused on the permanent employees that worked at PT. Angkasa Pura I (Persero). Analysis of the data was used descriptive qualitative and quantitative including instruments data test, the classic assumption test, multiple regression analysis, correlation and coefficient of determination and hypothesis test partial and simultaneous. The results of this study that showed the partial test results and simultaneous between the independent variables are financial compensation (X1) and nonfinancial compensation (X2) to the dependent variable is the employee performance (Y) which has a positive and significant impact to overall the formulating of research hypothesis was resolved. Through the test results of coefficient determination is known that variable financial compensation and non-financial compensation can explain by employee performance at 60%. Multiple Linear Regressions showed that the independent variable has positive coefficient values respectively is 0306 and 0608 with financial compensation as independent variables were the most dominating in affecting the employees’ performance at PT. Angkasa Pura I (Persero) Ngurah Rai International Airport in Bali.